OLAHRAGA SEPAK BOLA SEBAGAI ANTISIPASI KECANDUAN GAME ONLINE PADA GENERASI MUDA - Burhan, Zakir; Ashari, L. Hasan; Nulhadi, Agus; Herlina, Herlina (LPPM Institut Pendidikan Nusantara Global, 2024)
Football is a very popular sport among the public. Of the 27 youngsters who participated in the activity, most asked questions related to online game addiction. The following are some ways to avoid online game addiction, namely: a) Limit the time to play games, b) Find a new hobby, and c) Put the gaming device outside the bedroom. From the enthusiasm of the target (young people in Janapria village), this activity has the potential to continue and continue to develop, both with the same and different PkM themes. This is due to the lack of similar activities in the village. The implementation of the activity was evaluated as a whole, including the planning, preparation, and implementation stages. The evaluation was carried out to record the shortcomings and advantages obtained from this activity. Furthermore, it is expected to be useful input for the progress and sustainability of further activities, both for lecturers and students who will carry out this activity. The results of this activity, among others, can be seen from the enthusiasm of the youth, most of whom can feel the benefits and provide positive value, then based on suggestions and input from the youth, further activities need to be held, so that children can evaluate the results that have been carried out and improve the quality of sports even better.